Corporate Moral Responsibility: What Can We Infer from Our Understanding of Organisations? - Wilmot, Stephen (Journal of business ethics, 2001)
The question of corporate moral responsibility – whether corporate bodies can be held morally responsible for their actions – has been debated by a number of writers since the 1970s. This discussion is intended to add to that debate, and focuses for that purpose on our understanding of the organisation. Though the integrity of the organisation has been called into question by the postmodern view of organisations, that view does not necessarily rule out the attribution of corporate agency, any more than the postmodern view of the person rules out the attribution of individual agency. The postmodern view is opposed to a reifying, metaphysical view of corporate agency, but a semantic view of corporate agency would seem to sit more comfortably with it. A bigger problem for the idea of corporate moral responsibility arises from the fact that in Kantian terms organisations are not ends in themselves. In that sense they are not like persons, and this must limit their autonomy, and their responsibility. This aspect of organisations also limits their punishability. For these reasons corporate moral responsibility must be seen as more limited than the responsibility of persons.